Improved nonlinear optical properties of 6-nitro-BIPS composited with graphene oxide or N719 and their photoswitchable behavior. (31st October 2017) - Yang, Y J Bill; Zhu, Nanyan; Pan, Bilin; Ma, Chunsheng; Zhou, Sanhua; Yang, Tao; Yang, Qingyu; Li, Yuting; Zhang, Qing; Wang, Jing; Yuan, Shen
Abstract: Two kinds of novel photochromic composites—6-nitro-BIPS/graphene oxide and 6-nitro-BIPS/N719 were synthesized by esterification reaction. Spectroscopic characterization confirms 6-nitro-BIPS is covalently attached to graphene oxide and N719 through ester linkages. Compared with the individual components and the mechanical mixtures, 6-nitro-BIPS/graphene oxide and 6-nitro-BIPS/N719 show improved nonlinear optical properties at 532 nm in nanosecond region, resulting from the photoinduced electrons and/or energy transfer. Moreover, these two composites exibit photoswitchable nonlinear optical behavior, which are therefore promising candidates for use in optoelectronic and photonic devices.